1996
DOI: 10.1002/hep.510230644
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide inhibits tumor necrosis factor ?, decreases nitric oxide synthesis, and ameliorates the hyperdynamic circulatory syndrome in portal-hypertensive rats

Abstract: A hyperdynamic circulatory state frequently is ob-Portal hypertension accompanied by anatomic or served in portal hypertension with liver failure or exten-functional portal-systemic shunting very often is assosive portal-systemic shunting. Tumor necrosis factor a ciated with a hyperdynamic circulatory state. The so-(TNF) causes marked hypotension in mammals by in-called hyperdynamic circulatory syndrome (HCS) is ducing nitric oxide synthesis and has been shown to play characterized by generalized vasodilatatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
43
1
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 24 publications
(5 reference statements)
3
43
1
2
Order By: Relevance
“…21 These findings could be explained by the differences in TNF-␣ blood concentration or activity at baseline between PHT and sham-operated rats. Sham-operated rats have low levels of TNF-␣ blood concentration or activity 20,21 that would not contribute to regulation of NOS and hence the systemic circulation. Our results of TNF-␣ expression in blood and stomachs of sham-operated rats support this contention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 These findings could be explained by the differences in TNF-␣ blood concentration or activity at baseline between PHT and sham-operated rats. Sham-operated rats have low levels of TNF-␣ blood concentration or activity 20,21 that would not contribute to regulation of NOS and hence the systemic circulation. Our results of TNF-␣ expression in blood and stomachs of sham-operated rats support this contention.…”
Section: Discussionmentioning
confidence: 99%
“…The same phenomenon was found in two previous studies. 20,21 Benoit et al 47 showed that increased portal venous pressure in PHT models is produced by both ''forward'' and ''backward'' flow mechanisms accounting for 40% and 60% of the pressure elevation, respectively. Increased ''forward'' flow results in hyperemia, and ''backward'' flow produces congestion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La causa exacta de estos cambios es desconocida, pero se cree que es el resultado de una disfunción autonómica con alteraciones funcionales de los receptores β-adrenérgicos (11) o de factores depresores cardiacos tales como endotoxinas o citoquinas, especialmente el TNF-α, que media la activación del óxido nítrico (NO) (12). La traslocación bacteriana intestinal desencadena un aumento de la síntesis de citoquinas proinflamatorias y una activación de la oxido nítrico sintetasa endotelial (eNOS) (13). Recientemente, West y cols.…”
unclassified
“…observaron un aumento de la producción de NO y sobreexpresión de eNOS inducido por TNF-α en ratas cirróticas con translocación bacteriana (14,15). Además, la inhibición del TNF-α mejora la circulación hiperdinámica de la hipertensión portal en ratas (13,16) y se ha observado un aumento de la producción del TNF-α en los ganglios linfáticos mesentéricos de pacientes con cirrosis descompensada sometidos a trasplante (17).…”
unclassified